2016
DOI: 10.4103/0971-5851.177010
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological profile and antibiotic susceptibility patterns of clinical isolates in a tertiary care cancer center

Abstract: Introduction:This increased risk of bacterial infections in the cancer patient is further compounded by the rising trends of antibiotic resistance in commonly implicated organisms. In the Indian setting this is particularly true in case of Gram negative bacilli such as Escherichia coli, Klebsiella pneumoniae and Acinetobacter spp. Increasing resistance among Gram positive organisms is also a matter of concern. The aim of this study was to document the common organisms isolated from bacterial infections in canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 17 publications
0
6
1
Order By: Relevance
“…[ 10 11 12 ] We found that E. coli and K. pneumoniae were the most frequent Gram-negative bacteria isolated from cancer patients. Despite some reports inconsistent with our findings,[ 11 13 14 15 ] still, there is controversy about the prevalence of common etiology of nosocomial infections in patients with cancer. However, some reasons may explain the observed discrepancies in etiology of nosocomial infections.…”
Section: Discussioncontrasting
confidence: 88%
“…[ 10 11 12 ] We found that E. coli and K. pneumoniae were the most frequent Gram-negative bacteria isolated from cancer patients. Despite some reports inconsistent with our findings,[ 11 13 14 15 ] still, there is controversy about the prevalence of common etiology of nosocomial infections in patients with cancer. However, some reasons may explain the observed discrepancies in etiology of nosocomial infections.…”
Section: Discussioncontrasting
confidence: 88%
“…Similar finding with rates of multidrug resistance organisms has been noted in a study from Mumbai. 1 2 However, fortunately, the antimicrobial profile of carbapenems (imipenem, meropenem, ertapenem) and aminoglycosides (gentamicin, amikacin, netilmicin) showed >50% sensitivity. Although a susceptibility of 50% is not enough for empirical treatment, for nonneutropenic patients, carbapenems can be an empirical choice of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of the recent advances made by medical science in cancer treatment, infections still remain a major cause of morbidity and mortality in patients diagnosed with cancer. 1 2 Cancer patients are often immunocompromised because of the disease process itself and also due to various interventions such as chemotherapy. In addition, there are usually other associated risk factors for acquiring infection such as long-term catheterization, mucositis due to cytotoxic agents, neutropenia, and stem-cell transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…4,5,6 Numerous studies in paediatric oncology units have raised concerns about the increase in resistant pathogens. 7,8,9,10 The National Institute for Communicable Diseases (NICD) carries out surveillance in South Africa and collates resistance data from both public-and private-sector laboratories, which it publishes annually. The data shows that resistance in general is increasing in certain gram-negative bacteria and yeasts.…”
Section: Introductionmentioning
confidence: 99%